Fuzzy logic gain-tuned adaptive second-order GI-based multi-objective control for reliable operation of grid-interfaced photovoltaic system - Vedantham, Srinivas; Kumar, Shailendra; Singh, Bhim; Mishra, Sukumar (IET generation, transmission & distribution, 2018)
This study presents the fuzzy logic integrator gain-tuned improved second-order generalized integrator (GI) for a double-stage grid-interfaced photovoltaic (PV) system. The proposed system includes the functionalities of feeding active power to the grid, power factor correction, grid currents balancing and system isolation under grid side faults. Moreover, the smooth system operation is ensured under weak distribution grids where grid voltage is subject to huge diversions. Furthermore, automatic protection scheme for the system under grid-side faults is also established with the proposed algorithm for increased reliability. The fuzzy-tuned GI provides advantages of efficient and effective extraction of load current fundamental component under steady-state and dynamic grid conditions. The non-linear frequency error variation is compensated here using fuzzy logic-based self-tuning integrator gain of the controller. The controller is improved to mitigate the possible DC component in the load current. The neutral current in the loads is nullified by using a four wire system. The adaptive DC bus voltage helps to minimize the switching losses and prevents unexpected tripping of the PV inverter. The system is experimentally verified using a prototype built in the laboratory.